Review: Pengaruh Pemberian Ekstrak Propoelix terhadap Morfologi Motilitas dan Jumlah Sel Spermatozoa Tikus Wistar Jantan yang Diinduksi oleh Monosodium Glutamat - Windya Nazmatur Rahmah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Giving MSG can reduce the morphological quality, motility, and count of spermatozoa. Propoelix extract as an antioxidant is evidently capable of a non-enzymatic radical scavenger. This research aims at evaluating the effect of propoelix extract administration on sperm quality of MSG-induced male Wistar rats. Employing the post the only control group design, 18 rats aged 3 months were divided into 3 random groups, weighing ±250 gram. Propoelix extract was given orally for 21 days and on 22 days, cauda epididymis until the ampulla of vas deferens was cut in a glass jar that has been given 0,5 cc of 0,9% physiological solution. The result of spermatozoa morphology (%) in group K (54,5) group P1 (65) group P2 (76) was significantly higher, p < 0,05. Spermatozoa motility (%) in group K (41.3) group P1 (53.8) group P2 (65.3) were significantly higher, p < 0.05. The number of spermatozoa cells (million/ml) in group K (2.65), group P1 (3.63), group P2 (4.91) was significantly higher, p < 0.05. Conculatition of propoelix extract was able to improve the quality of the morphology, motility, and the count of spermatozoa of MSG-induced male Wistar rats.